2004
DOI: 10.1061/(asce)0899-1561(2004)16:6(597)
|View full text |Cite
|
Sign up to set email alerts
|

Treatments for the Improvement of Recycled Aggregate

Abstract: The microstructure of recycled aggregate prepared from the crushing of old concrete was studied. It was found that the recycled aggregate is covered with loose particles that may prevent good bonding between the new cement matrix and the recycled aggregate. The old cement paste that remained on the natural aggregate was porous and cracked, leading to weak mechanical properties of the recycled aggregate. Treatment of the recycled aggregate by impregnation of silica fume solution and by ultrasonic cleaning was s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
155
0
13

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 442 publications
(174 citation statements)
references
References 3 publications
6
155
0
13
Order By: Relevance
“…4, At the early age, with the support of treatment solution type S, the compressive strength of RAC strongly soared up about 23-50% compared to untreated RAC, and it was around 1.7-6.9% higher than that of NAC. This observation indicated that the combination between solution type S and pozzolanic materials promoted the increase of the compressive strength of RAC at the early age more effectively than other methods [29]. At 28 days (see Fig.…”
Section: Compressive Strengthmentioning
confidence: 81%
See 1 more Smart Citation
“…4, At the early age, with the support of treatment solution type S, the compressive strength of RAC strongly soared up about 23-50% compared to untreated RAC, and it was around 1.7-6.9% higher than that of NAC. This observation indicated that the combination between solution type S and pozzolanic materials promoted the increase of the compressive strength of RAC at the early age more effectively than other methods [29]. At 28 days (see Fig.…”
Section: Compressive Strengthmentioning
confidence: 81%
“…In addition, the results revealed that RAC treated with 20SSF had the highest value in compressive strength of concretes in comparison with other specimens and was comparable with that of NAC. Therefore, the combination between sodium silicate and silica fume created a good treatment solution for RCA which was higher than the existing method [29]. It could be explained that silica fume contained the high percentage of amorphous silica which was useful for the development of concrete strength [32] and silica fume in concrete gave the higher strength compared to that of fly ash [33].…”
Section: Compressive Strengthmentioning
confidence: 99%
“…Weak interfacial transition zone (ITZ) between the recycled concrete aggregate (RCA) and the cement matrix has also been identi ed [1,9,10]. Moreover, the presence of more than one ITZ in the RAC is another reason for the low quality of the RAC [1,9,11].…”
Section: Introductionmentioning
confidence: 99%
“…Silica fume acts as a micro filler, filing the transition zone between the aggregate surface and the bulk cement matrix, followed by pozzolanic reaction at the same place [13] . When porous aggregate is involved, as in lightweight aggregate used in this study, the interfacial transition zone extends from a certain distance below the surface of the aggregate particle out to the bulk cement [14] . Finally, it can be concluded that incorporating silica fume in structural lightweight concrete mixes significantly reduces the chloride ion penetration dye to the above mentioned mechanism (filler and pozzolanic effects) of concrete.…”
Section: Introductionmentioning
confidence: 99%